2023
DOI: 10.1001/jamanetworkopen.2023.45299
|View full text |Cite
|
Sign up to set email alerts
|

Patent Ductus Arteriosus and Bronchopulmonary Dysplasia–Associated Pulmonary Hypertension

Eduardo Villamor,
Elke van Westering-Kroon,
Gema E. Gonzalez-Luis
et al.

Abstract: ImportanceBronchopulmonary dysplasia (BPD) is often associated with pulmonary vascular disease and secondary pulmonary hypertension (PH). The pathogenesis of BPD-associated PH (BPD-PH) is complex and involves prenatal and postnatal factors that disrupt pulmonary vascular development, and patent ductus arteriosus (PDA) is a factor potentially associated with risk of BPD-PH that has been identified in very recent studies.ObjectiveTo explore the association of PDA with BPD-PH using a bayesian model-averaged (BMA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 93 publications
0
0
0
Order By: Relevance
“…Although single‐center observational studies have shown no association between BPD and small PDA, the association is apparent when the shunt persists for 7–14 days across PDA. Although studies have shown an association between moderate‐severe PDA and BPD, treating the PDA has not shown consistent results in the reduction of BPD and is a matter of debate 13,14 . In our cohort, there was an association; efficacy needs to be proven in large clinical trials.…”
Section: Discussionmentioning
confidence: 63%
“…Although single‐center observational studies have shown no association between BPD and small PDA, the association is apparent when the shunt persists for 7–14 days across PDA. Although studies have shown an association between moderate‐severe PDA and BPD, treating the PDA has not shown consistent results in the reduction of BPD and is a matter of debate 13,14 . In our cohort, there was an association; efficacy needs to be proven in large clinical trials.…”
Section: Discussionmentioning
confidence: 63%